2018
DOI: 10.1159/000493449
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin-Daumone Hybrid Inhibits Cancer Cell-Mediated Osteolysis by Targeting Cancer Cells and Osteoclasts

Abstract: Background/Aims: Bone metastasis of cancer cells decreases patient survival and quality of life. Hybridization via the covalent coupling of two bioactive natural products is a useful strategy for developing more potent anticancer agents by enhancing their bioavailability and avoiding drug resistance. Methods: The in vivo activities of artemisinin-daumone hybrid 15 (ARTD) were estimated in cancer cell-inoculated mice and ovariectomized mice. The viability, migration, and invasion of cancer cells were measured v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 46 publications
(27 reference statements)
1
16
0
Order By: Relevance
“…This transcript factor has been confirmed to be strongly associated with aggressiveness and resistance to cancer therapies (Zhang et al, 2020). Ma et al found that ARTdaumone hybrids inhibited cancer cell-mediated osteolysis by upregulating the level of activating transcription factor 3 and downregulating the level of E2F transcription factor 1 and hepatocyte nuclear factor 4 alpha (Ma et al, 2018). Li et al found that ART-chemotherapeutic conjugates inhibited the growth and proliferation of ovarian cancer cells, resulting in S-phase arrest, apoptosis and epithelial mesenchymal transition (EMT) (Li et al, 2016).…”
Section: Hybrid Derivativesmentioning
confidence: 96%
See 2 more Smart Citations
“…This transcript factor has been confirmed to be strongly associated with aggressiveness and resistance to cancer therapies (Zhang et al, 2020). Ma et al found that ARTdaumone hybrids inhibited cancer cell-mediated osteolysis by upregulating the level of activating transcription factor 3 and downregulating the level of E2F transcription factor 1 and hepatocyte nuclear factor 4 alpha (Ma et al, 2018). Li et al found that ART-chemotherapeutic conjugates inhibited the growth and proliferation of ovarian cancer cells, resulting in S-phase arrest, apoptosis and epithelial mesenchymal transition (EMT) (Li et al, 2016).…”
Section: Hybrid Derivativesmentioning
confidence: 96%
“…This approach is often used in searching for safe, effective and specific innovative medicines for cancer therapy (Letis et al, 2017;Yu et al, 2018;Zborovskii et al, 2018). Many studies of ARTs have generated new hybrids, such as ART-derivative-N-heterocyclic carbene (NHC)-gold(I)hybrids (Zhang et al, 2020), ART-daumone hybrids (Ma et al, 2018), DHA-bile acid hybrids (Letis et al, 2017;Marchesi et al, 2019), DHA-cinnamic acid hybrids (Xu et al, 2016), DHAcoumarin hybrids (Yu et al, 2018) and ART-chemotherapeutic agent conjugates (Li et al, 2016), et al, with more potent activity than with either agent alone ( Table 1). We designed and synthesized DHA-cinnamic acid ester derivatives modified at two positions, C-9 and C-12.…”
Section: Hybrid Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Artemisinin, a kind of sesquiterpene lactone endoperoxide, is extracted from tranditional Chinese herb Artemisia annua . Nowadays, new artemisinin‐based treatments are applied in the treatment of other diseases, and a substantial amount of artemisinin is required to meet the clinical treatment (Wu et al ., 2016; Kayentao et al ., 2018; Ma et al ., 2018). Although artemisinin and its precursor artemisinic acid have been synthesized in several species, like yeast, Escherichia coli , Nicotiana benthamiana , and Physcomitrella patens , plant‐derived artemisinin is still an essential and economical choice due to the limited production from synthetic methods (Martin et al ., 2003; Paddon et al ., 2013; Wang et al ., 2016; Khairul et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, RT Profiler PCR array has been used by many scholars to explore the diagnostic targets of other tumors in recent years, and a lot of achievements have been made. [12][13][14] Bioinformatics is a new discipline emerging with the launch of the human genome project, 15 and has established a fundamental position in the life sciences. Mining and analyzing the massive data based bioinformatics also allow us to screen key genes or pathways associated with the diseases.…”
Section: Introductionmentioning
confidence: 99%